Effective Factor Analysis for Chromium(VI) Removal from Aqueous Solutions and Its Application to Tunçbilek Lignite Using Design of Experiments - Âli Yurdun Orbak; İlkün Orbak (Journal of Chemistry)
Poisonous heavy metals in air, water, and soil produce global environmental problems that are considerable threats to humankind. To meet the local and international guidelines for heavy metal release, companies often use different approaches, such as chemical precipitation, chelating agents, or activated carbon produced by adsorption. One of these heavy and toxic metals is chromium(VI). Chromium(VI) is commonly used in many applications, such as dye fixation in the textile industry or as an anticorrosive agent in paints. The aim of this paper is to explore the factors affecting the removal of one of these deadly heavy metals, chromium(VI), from aqueous solutions. For this purpose, activated carbon from Turkish Tunçbilek lignite is prepared with both chemical and physical activation methods to investigate the adsorption behavior of chromium(VI). The effects of initial chromium(VI) concentration, adsorption temperature, and pH on adsorption are studied using a design of experiments method with a full 24 factorial design with center points. The Freundlich and Langmuir adsorption isotherms that are commonly used in chemical engineering are also applied both for predicting the amount of chromium(VI) adsorbed and confirming the validity and advantages of the obtained regression model. The results indicate that the design of experiments and regression can explain and support the design of new materials by using linear and physically meaningful equations instead of local nonlinear and empirical models that are usually insufficient. Additionally, three experiments were carried out in the liquid phase to test the activated carbon samples: chromium, chromium and sucrose, and chromium-sucrose-ion. A change in adsorption capacities of the activated carbon samples was observed. Sucrose was chosen for the experiments because it contains six carbon atoms in a slightly soluble structure. The results indicated that Tunçbilek lignite exhibits good adsorption capability.